Sexual morphs and colour variants of Aphis (formerly Toxoptera) odinae (Hemiptera, Aphididae) in Japan - Blackman, Roger L.; Sorin, Masato; Miyazaki, Masahisa (Zootaxa, 2011)
Recent molecular studies have shown that the genus Toxoptera is polyphyletic, and in particular that the name of the aphid known since 1952 as Toxoptera odinae (van der Goot) should revert to Aphis odinae (van der Goot), stat. rev. In this paper oviparae, alate males and fundatrices of A. odinae are described for the first time, from Japan. A. odinae is common as a grey-brown or rust-brown aphid on numerous plant species of shrubby habit throughout the Old World tropics and subtropics, but in temperate east Asia much darker forms occur, and Japanese populations of A. odinae include a dark green form not found elsewhere in the world. Multivariate morphometrics were used to confirm that both colour forms of the aphid in Japan were conspecific with samples from other parts of the world. Pergandeida kalopanacis Hori 1927 is a new synonym of A. odinae.